The effectiveness of developing culture-based mathematics learning media through visual basic application - Hidayat, Wahyu; Linda, Linda (Universitas Papua, 2023)
Learning media in the process of teaching and learning mathematics have been found in Indonesia. However, learning media with cultural approach nuances are still difficult to find. This shows that the need for learning media to integrate the culture in learning mathematics. Technological developments have changed all fields, including culture. Culture-based mathematics learning through Visual Basic Application (VBA) media has not been studied much, so it is hoped that it can overcome problems in learning mathematics to improve students' mathematical reasoning abilities and ultimately preserve culture. This study aims to develop culture-based mathematics learning media through VBA, which has a good level of validation, practicality, and effectiveness. The research method used is development research using the Plomp model, which includes the initial investigation, design, and assessment phase. The subjects of this study were 34 students of class IX-A from one of the junior high schools in Indonesia. The instrument used was a test containing a description test of 4 questions based on indicators of reasoning ability and a non-test instrument containing student questionnaires and interview instruments. The media developed in this study were analyzed through validity and practicality in order to obtain valid and practical media. The results showed that culture-based mathematics learning media had very valid quality criteria (84.5%), we're very practical (82.14%), and potentially influenced the development of students' mathematical reasoning abilities (80.65%). In addition, teachers and students showed a positive response to the implementation of learning. This indicates that culture-based mathematics learning media through VBA is a feasible alternative to be used and developed in mathematics learning. This has the impact that through learning with cultural nuances, student ethics will be better, mutual respect, respect, and even culture can be preserved. Thus, learning culture-based mathematics through VBA is very effectively used in learning curvature material.